Pertumbuhan dan Produksi Beberapa Varietas Kedelai (Glycine max (L.) Merrill) terhadap Pemberian Kompos Limbah Jerami Padi Diperkaya Kotoran Kambing - Rizky, Muhammad; Sajar, Suryani; Hakim, Tharmizi (JURNAL PERTANIAN KEPULAUAN, 2025)
The purpose of this study was to determine how several varieties of soybean (Glycine max (L.) Merrill) responded to the provision of composted rice straw waste to enrich goat manure in terms of growth and production. This study used a factorial randomized group design, a method with two factors and three replications. In this study, the first factor was soybean variety (V) divided into four parts, such as V1=Grobogan Soybean Variety, V2=Anjasmoro Soybean Variety, V3=Devon Soybean Variety, and V4=Wilis Soybean Variety. The second factor is grouped from K0 = 0 kg/plot, K1 = 1 kg/plot, K2 = 2 kg/plot, and K3 = 3 kg/plot as four components of rice straw waste compost enriched with goat manure. Meanwhile, the parameters that became the object of research were plant height (cm), number of productive branches, stem diameter (mm), number of pods, number of filled pods, number of empty pods, and weight of 100 seeds. The results explained that the growth response of soybean varieties influenced plant height, number of pods, number of filled pods, number of empty pods, seed production, and 100-seed weight. In contrast, the number of productive branches and stem diameter had no effect. Giving rice straw compost enriched with goat manure affects the number of productive branches and the number of filled pods, while plant height, stem diameter, number of pods, number of empty pods, seed production, and 100 seed weight do not have an effect. The interaction between the application of several varieties of soybean plants and composted rice straw waste enriched with goat manure did not show a significant effect on all parameters of the growth and production of soybean plants.